2020
DOI: 10.17509/ije.v13i1.24715
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Teachers’ Practices on Formative Assessment Scale (TPFAS): A Measure Using Feedback Loop Model

Abstract: This study aimed to develop and validate an instrument regarding teachers’ practices on formative assessment using the elements of the Feedback Loop Model. A pilot study was surveyed to 157 science teachers on how frequently they practice formative assessments in their Science classes. Teachers’ responses were analyzed using Cronbach’s alpha statistics on the Feedback Loop constructs and Confirmatory factor analysis for the entire instrument. Findings suggest that with the deletion of 10 survey items from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The positive impact of FLM in AFL on overall student learning outcomes is supported by Ole [31], as it provides quality feedback based on assessment criteria, motivating students to improve their learning performance. Furthermore, teacher involvement in implementing AFL can foster the development of students' critical thinking abilities, creativity, and self-efficacy [29].…”
Section: Student Engagement In Learningmentioning
confidence: 99%
“…The positive impact of FLM in AFL on overall student learning outcomes is supported by Ole [31], as it provides quality feedback based on assessment criteria, motivating students to improve their learning performance. Furthermore, teacher involvement in implementing AFL can foster the development of students' critical thinking abilities, creativity, and self-efficacy [29].…”
Section: Student Engagement In Learningmentioning
confidence: 99%
“…Data collection was retrieved using Google forms before and after the webinar series. With the instruments called Teachers' Conceptions and Practices of Formative Assessment Questionnaire by Yan and Cheng (2015) that measured teachers' affective and instrumental attitudes and self-efficacy toward FA and Teachers' Practices on Formative Assessment Scale: A measure using Feedback Loop by Ole (2020) that focused on the FA classroom practices based on FLM, relevant information needed in the study were systematically analyzed and interpreted accordingly.…”
Section: Research Instrumentmentioning
confidence: 99%
“…where s pertains to the scores assigned by each rater minus the lowest score in the used category (r = rating by an expert and lo = the lowest possible validity rating); n is the number of raters and experts; and c is the number of categories that raters can choose. According to the table recommended by Aiken (particularly on four (4) number of experts and raters and using five (5) number of rating categories --see table V, Aiken, 1985:134), the content validity coefficient (V value) of all the items in the checklist must be falling at 0.88 or higher to effectively reach a significant standard (Ole, 2020). Consequently, as reflected in Table 1, experts found that the items were valid because of a content coefficient value close to 1.00 (V= 0.94).…”
Section: Content Validation and Pilot Testingmentioning
confidence: 99%